Magaḷige tandeya ōligaḷu : sacitra, makkaḷigāfi jagattina prācīna kālada saṅkṣipta vrttānta - Nehru, Jawaharlal, 1889-1964 (SAMP early 20th-century Indian books project, 1952)
Translation of collection of letters from a former prime minister of India to his young daughter, Indira Gandhi, dealing with the beginnings of the Earth, man's awareness of himself, and history and civilization of the ancient world.